1989
DOI: 10.1103/physrevlett.63.39
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of superfluid vortex line density behind a heat (second-sound) pulse in helium II

Abstract: A new probe for superfluid vortex line density with a response time of 400 /is and a spatial resolution of 1 mm was developed and used to investigate the growth and decay of superfluid vortex lines during the passage of a heat pulse. The evolution process turns out to be in accordance with existing theories. PACS numbers: 67.40.Pm, 67.40.Vs One of the most striking features of liquid-helium II is its high thermal conductivity, resulting from an internal convection process that can be described in terms of Tisz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 15 publications
(1 reference statement)
0
3
0
Order By: Relevance
“…Selected typical experimental findings are correlated with theoretical calculations based on a simple model deduced for the case of steady flow in tubes. Some previous results have been already published by Fiszdon & Schwerdtner (1989) and Schwerdtner, Stamm & Schmidt (1989).…”
Section: Introductionmentioning
confidence: 54%
“…Selected typical experimental findings are correlated with theoretical calculations based on a simple model deduced for the case of steady flow in tubes. Some previous results have been already published by Fiszdon & Schwerdtner (1989) and Schwerdtner, Stamm & Schmidt (1989).…”
Section: Introductionmentioning
confidence: 54%
“…Nonlinear theory about second sound wave was first developed by Temperley [3], and was then extended by Khalatnikov [4,5] whose prediction was proven by the experimental demonstration of Dessler and Fairbank [6]. Planar second sound wave has been frequently used to probe quantized vortices for its relatively simple geometry, and extensive study concerning this topic has been carried out in recent decades [7][8][9][10]. It has been shown that second sound wave interacts with self-generated quantized vortices as it propagates along a wave guide.…”
Section: Introductionmentioning
confidence: 99%
“…At 1.65 K, ␣ / ␤ is measured 24 to be 109 s cm −2 , and the counterflow velocity is nearly the same as the velocity of the normal fluid. Equation ͑12͒ then gives a line density of 3 ϫ 10 5 cm −2 .…”
Section: Resultsmentioning
confidence: 93%